2015
DOI: 10.1071/ma15041
|View full text |Cite
|
Sign up to set email alerts
|

Necrotic enteritis in chickens: an important disease caused by Clostridium perfringens

Abstract: Clostridium perfringens, a spore-forming, Gram-positive, anaerobic bacterium, causes a variety of diseases throughout the animal kingdom. Each disease in each animal species tends to be caused by particular strains of C. perfringens and is defined by the tissue tropism and toxin profile of the bacteria. In chickens toxinotype A strains cause necrotic enteritis; a disease characterised by tissue damage to the proximal regions of the small intestine. In extreme cases the disease can be lethal but is more commonl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…It is ubiquitous in nature and can be found as a normal component of soil, contaminated food, decaying vegetation, marine sediment, intestinal tract of birds and poultry litter. The C. perfringens type A causes necrotic enteritis (NE) in poultry ( Longo et al., 2010 , Opengart and Songer, 2013 , Moore, 2015 ), the acute form of the disease causes high mortality in broiler birds ( Kaldhusdal and Lovland, 2000 ), where as the subclinical form causes erosion of intestinal mucosa results in decreased digestion and absorption, depressed weight gain and increased FCR ( Kaldhusdal et al., 2001 , Hofacre et al., 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is ubiquitous in nature and can be found as a normal component of soil, contaminated food, decaying vegetation, marine sediment, intestinal tract of birds and poultry litter. The C. perfringens type A causes necrotic enteritis (NE) in poultry ( Longo et al., 2010 , Opengart and Songer, 2013 , Moore, 2015 ), the acute form of the disease causes high mortality in broiler birds ( Kaldhusdal and Lovland, 2000 ), where as the subclinical form causes erosion of intestinal mucosa results in decreased digestion and absorption, depressed weight gain and increased FCR ( Kaldhusdal et al., 2001 , Hofacre et al., 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…The PCRbased detection of α toxin is essential for the typical identification of α toxigenic C. perfringens strains (Baums et al, 2004). Several Clostridia enteric diseases occur in poultry, but probably the most common and severe one is NE, caused by C. perfringens type A (Moore, 2015). In Sweden, Engstrom et al (2003) demonstrated that all C. perfringens strains were classified as type A without enterotoxin genes.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that C. perfringens type A induces intestinal mucosal damage in chickens (Moore, 2015). The α toxin producing C. perfringens is phospholipase C sphingomyelinase that hydrolyzes lecithin into phosphorylcholine and diglyceride and as a consequence induces the production of inflammatory mediators causing blood vessel contraction, platelet aggregation, myocardial dysfunction, and finally acute death (Matsuda et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…In poultry, toxinotype A strains of C. perfringens is considered to be the causative agent of necrotic enteritis (NE), however, to a minor extent, toxinotype C is also accountable for this disease occurrence. The disease is characterized by the damage of tissue in the proximal part of the small intestine (Guran and Oksuztepe, 2013;Moore, 2015;Swayne et al, 2013). Usually, the number of C. perfringens in the intestinal content is low (approximately 10 4 CFU/g of ingesta).…”
Section: Introductionmentioning
confidence: 99%